32nd AIAA Applied Aerodynamics Conference 2014
DOI: 10.2514/6.2014-2270
|View full text |Cite
|
Sign up to set email alerts
|

USM3D predictions of Supersonic Nozzle Flow

Abstract: This study focused on the NASA Tetrahedral Unstructured Software System CFD code (USM3D) capability to predict supersonic plume flow. Previous studies, published in 2004 and 2009, investigated USM3D's results versus historical experimental data. This current study continued that comparison however focusing on the use of the volume souring to capture the shear layers and internal shock structure of the plume. This study was conducted using two benchmark axisymmetric supersonic jet experimental data sets. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For the flow solution cases conducted in this study, either the S-A or the k-ε turbulence model with Sarkar's compressibility and pressure dilation was used. 3,13 This variant of k-ε model was shown to work well for modeling supersonic jets in references 3 and 13.…”
Section: B) Cfd Code Informationmentioning
confidence: 97%
See 2 more Smart Citations
“…For the flow solution cases conducted in this study, either the S-A or the k-ε turbulence model with Sarkar's compressibility and pressure dilation was used. 3,13 This variant of k-ε model was shown to work well for modeling supersonic jets in references 3 and 13.…”
Section: B) Cfd Code Informationmentioning
confidence: 97%
“…Adequate cell density is also needed to accurately capture the core length and the shock structure. A past study 3 showed that five cylindrical sources for the nozzle and the field provided adequate grid density for capturing the jet plume. A series of line sources are also placed on the nozzle lip to enable a smooth start of the shear layer.…”
Section: A) Grid Generationmentioning
confidence: 99%
See 1 more Smart Citation